The impacts of trust, cost and risk on collaboration in environmental governance. Issue 3 (7th June 2020) - Bodin, Örjan; Baird, Julia; Schultz, Lisen; Plummer, Ryan; Armitage, Derek
Abstract: Collaborative approaches to environmental governance are drawing increased interest in research and practice. In this article we investigate the structure and functioning of actor networks engaged in collaboration. We specifically seek to advance understanding of how and why collaborative networks are formed as actors engage in addressing two broad classes of collective action problems: coordination and cooperation. It has been proposed that more risk‐prone cooperative problems favour denser and more cohesive bonding network structures, whereas less risky coordination problems favour sparser and more centralized bridging structures. Recent empirical findings, however, cast some doubts on these assumptions. In building on previous work we propose and evaluate a set of propositions in order to remedy these ambiguities. Our propositions build on the assumption that bridging structures could, if actors experience sufficient levels of trust in the collaborative process, adequately support both cooperation and coordination problems. Our empirical investigation of four UNESCO Man and Biosphere Reserves gives initial support for our assumptions, and suggests that bridging structures emerge when actors have trust in the collaborative endeavour, and/or when the cost of collaborative failure is deemed low. While caution is warranted due to data limitations, our findings contribute to improved policies and guidelines on how to stimulate and facilitate more effective collaborative approaches to environmental governance. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article